HSP70-Inducible hNIS-IRES-eGFP Reporter Imaging: Response to Heat Shock - Jiantu Che; Mikhail Doubrovin; Inna Serganova; Lyudmila Ageyeva; Tatiana Beresten; Ronald Finn; Ronald Blasberg (Molecular Imaging)
A retroviral vector pQHSP70/hNIS-IRES-eGFP (pQHNIG70) was constructed containing the hNIS-IRES-eGFP dual-reporter genes under the control of an inducible human heat shock protein (HSP)70 promoter and RG2-pQHSP70/hNIS-IRES-eGFP (RG2-pQHNIG70) transduced cells were generated. Heat-induced expression of both reporter genes in RG2-pQHNIG70 cells was validated by enhanced green fluorescent protein (eGFP) fluorescence-activated cell sorter, in vitro radiotracer assays, and immunoblot and immunocytochemistry. A 2.2- to 6.1-fold ( 131 I − ), a 6.1- to 14.4-fold ( 99m TcO 4 − ), and a 5.1- to 39-fold (fluorescence) increase above baseline was observed in response to graded hyperthermia (39–43°C). Increases in eGFP fluorescence and radiotracer uptake were first noted at 6 hours, reached a maximum at 24 hours, and fell toward baseline at 72 hours. A stable ratio of radiotracer uptake to eGFP fluorescence and to heat shock protein (HSP)70 protein was demonstrated over a wide range of expression levels, induced by different levels of heating. We also demonstrate that the local application of heat on RG2-pQHNIG70 xenografts can effectively induce hNIS and eGFP gene expression in vivo and that this expression can be efficiently visualized by fluorescence, scintigraphic, and micro–positron emission tomography imaging. Endogenous HSP70 protein and reporter expression was confirmed by postmortem tissue evaluations (immunoblot and immunohistochemistry). The pQHNIG70 reporter system can be used to study stress and drug responses in transduced cells and tissues.